A Measure for Assessing Academic Virtues and Strengths in the University Setting: Construction and Initial Examination of Structure and Correlates - Green, Zane Asher; Karuppannan, Gunasegaran (2025)
This research demonstrates the construction and preliminary examination of the structure of a domain-specific measure, namely the Character Strengths Scale for University Students (CSSUS). Reflecting the use of the 24 Values in Action (VIA) strengths in the study domain, the CSSUS likely adds greater specificity to the findings pertinent for devising and implementing meaningful strategies for furthering academic development, student learning, and well-being in higher education. Derived from best practices, the item generation process of the CSSUS was based on four steps: (1) identification of the domain, (2) item generation, (3) content validity, and (4) field pre-testing of the items of the CSSUS. The initial examination of the factors of the CSSUS was based on a sample of 540 undergraduate and graduate students studying in Lahore, Pakistan. Results provided evidence of a four-factor structure of the CSSUS. Furthermore, the CSSUS and its subscales were positively related to academic achievement and the measures of satisfaction with life, positivity, and student self-efficacy. In addition, the CSSUS and its subscales were negatively related to the measure of academic burnout. The correlations provided evidence of the concurrent criterion-related validity of the scale. Moreover, female students reported higher levels of love and spirituality, whereas male students higher levels of leadership, creativity, and bravery. Also, there was no significant difference in the use of academic virtues with regard to gender, level of education (undergraduate and graduate), study discipline (agricultural sciences, humanities, health sciences, and engineering technology), type of university (public and private), and level of academic performance (low, medium, and high). The theoretical contribution and practice implications of the results are discussed. Limitations of the study and prospects for future research are also discussed.